Diagnostic performance of standardized typical CT findings for COVID-19: a systematic review and meta-analysis - Bo Da Nam; Hyunsook Hong; Soon Ho Yoon (Insights into Imaging, 2023)
Abstract Objective To meta-analyze diagnostic performance measures of standardized typical CT findings for COVID-19 and examine these measures by region and national income. Methods MEDLINE and Embase were searched from January 2020 to April 2022 for diagnostic studies using the Radiological Society of North America (RSNA) classification or the COVID-19 Reporting and Data System (CO-RADS) for COVID-19. Patient and study characteristics were extracted. We pooled the diagnostic performance of typical CT findings in the RSNA and CO-RADS systems and interobserver agreement. Meta-regression was performed to examine the effect of potential explanatory factors on the diagnostic performance of the typical CT findings. Results We included 42 diagnostic performance studies with 6777 PCR-positive and 9955 PCR-negative patients from 18 developing and 24 developed countries covering the Americas, Europe, Asia, and Africa. The pooled sensitivity was 70% (95% confidence interval [CI]: 65%, 74%; I 2 = 92%), and the pooled specificity was 90% (95% CI 86%, 93%; I 2 = 94%) for the typical CT findings of COVID-19. The sensitivity and specificity of the typical CT findings did not differ significantly by national income and the region of the study (p > 0.1, respectively). The pooled interobserver agreement from 19 studies was 0.72 (95% CI 0.63, 0.81; I 2 = 99%) for the typical CT findings and 0.67 (95% CI 0.61, 0.74; I 2 = 99%) for the overall CT classifications. Conclusion The standardized typical CT findings for COVID-19 provided moderate sensitivity and high specificity globally, regardless of region and national income, and were highly reproducible between radiologists. Critical relevance statement Standardized typical CT findings for COVID-19 provided a reproducible high diagnostic accuracy globally. Key points Standardized typical CT findings for COVID-19 provide high sensitivity and specificity. Typical CT findings show high diagnosability regardless of region or income. The interobserver agreement for typical findings of COVID-19 is substantial. Graphical abstract